FACTORS ASSOCIATING THE IT CAPABILITY IN HEALTHCARE SERVICES & IT'S PERCEIVED TRANSFORMATION IMPACT: AN EMPIRICAL STUDY OF THE HEALTHCARE SECTOR IN MALAYSIA - RATNAM, KALAl ANAND (2014)
Health care providers in Malaysia are facing the challenges linking clinical administrative processes to ensure that an effective collaboration and efficient delivery of care are in place. The challenge is influenced by the state of the current Health Information Technology (HIT) infrastructure & Hospital Information & Management Systems (HIMS) deployed across hospitals in Malaysia that are typically confined within a particular healthcare provider without any sort of sharing and integration across other healthcare service providers and its associates. The electronic health digital information which is currently available in major public healthcare providers is only accessible internally resulting in duplication and access difficulty across other healthcare providers and its associates such as insurance providers and medical research agencies. As health Information technology rapidly evolves with large data sets, current storage and resources needs to be relooked at, as it may potentially limit the process of decision-making and other related healthcare activities